Islamic Commercial Bank Performance: The Nexuses by Financial Ratios, Macro Economics, And Financial Technology - Nurlaili, Rahma; Miranti, Titis (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2023)
The objective of this study is to examine the relationship between various factors and the performance of Islamic commercial banks in Indonesia over the next 12 periods. The variables considered include Non-Performing Assets, Capital Adequacy Ratio, Insolvency-risk, Inflation, Financial Technology, and Bank Size. The research methodology employed is a quantitative approach with a descriptive analysis. The sampling technique utilized is saturated sampling, resulting in a total of 96 data points. The findings indicate that the Non-Performing Assets (NPA) variable has a significant impact on Return on Assets (ROA), while the ROA variable does not significantly affect the NPA variable. Additionally, the inflation variable does not have a statistically significant effect on ROA, and vice versa. In the short term, the variables that influence bank performance are NPA, Capital Adequacy Ratio, Insolvency-risk, Financial Technology, and Bank Size. In the long term, significant factors influencing bank performance are NPA, Insolvency-risk, Financial Technology, and Bank Size. The Impulse Response Function (IRF) test demonstrates that ROA shows a positive response to the impact of NPA, Capital Adequacy Ratio, Inflation, Financial Technology, and Bank Size, while it exhibits a negative response to shocks caused by inflation. Throughout the study period, the variable with the greatest contribution remains Financial Technology, followed by other variables. Ultimately, the aim of this study is to provide insights for future policy implementation and decision-making within companies